Apakah Integritas Memodersi Kecerdasan Emosional, Kompetensi dan Independensi terhadap Kualitas Audit? - Yulia Monica Ristanti; Sutrisno Sutrisno; Sari Atmini (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to analyze the influence of emotional quotient, competence, and independence, by involving auditor integrity as a moderating influence on audit quality. Methodology/approach: The population in this study consists of all levels of auditors working in Public Accounting Firms in the cities of Malang and Surabaya. Sampling was conducted using a non-probability method with purposive sampling technique. The number of samples obtained was 98 respondents. This study used primary data collected through questionnaire distribution. Data were analyzed using Structural Equation Model-Partial Least Square (SEM-PLS) with the assistance of SmartPLS version 4. Findings: The results of this study indicate that auditor competence and independence have a positive effect on audit quality. Meanwhile, the auditor's emotional quotient does not affect on audit quality. Auditor integrity as a moderating in this study can strengthen the relationship between emotional quotient, competence, and independence on audit quality among auditors in the cities of Malang and Surabaya. Practical and Theoretical contribution/Originality: This study can provide practical guidelines for auditors in Public Accounting Firms in evaluating policies or performance that can be done to maintain and enhance the quality of their audit results, as well as to maintain public trust. Thus, through continuous improvement in audit quality, clients can make informed decisions based on reliable, trustworthy financial reports produced by auditors. Additionally, this research can explain existing theories into a phenomenon, namely Heider's attribution theory (1958) and Jensen and Meckling's agency theory (1976), and provide empirical evidence regarding factors influencing audit quality. Research Limitation: This study utilized a Google Form link to distribute questionnaires to respondents who were inaccessible. This resulted in less direct knowledge of to whom the questionnaire was distributed and how many questionnaires were distributed.